Design, implementation and evaluation of a learning content management system - Şimşek, Hüseyin. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2006., 2006)
Learning content management systems (LCMS) are designed to enable subject matter experts to design, to create, to deliver and to measure the result of e-learning courses quickly. LCMS applications offer a scalable platform to deliver proprietary knowledge to individual learners. This study aims to develop and to implement a SCORM compliant LCMS that can be used by educators with varying degrees of background knowledge on educational technologies. Therefore, the study will mainly focus on understanding the usability of the developed system among students at the faculty of education with varying degrees of computer literacy. In order to anticipate usability problems and errors as early as possible in the software development process, two usability studies were conducted, namely beta and validation study. Beta study had been conducted at the late development phase of the system and aimed to test BU-LCMS with target user groups performing representative tasks to ensure able/functional product. The system and data collection tools were also revised according to the results of the beta study. After completing the revisions that beta study results emphasized, a validation study, conducted at the end of the development process, aimed to verify that BU-LCMS meets previously identified users needs. The results of the study indicated significant improvements in mean usability scores from the beta to the validation study, indicating that the assessments and revisions following the beta version were effective in improving the usability needs. Furthermore, in order to show that BU-LCMS could effectively be used by different groups of educators, the mean of usability scores calculated for different groups and results showed that there is not statistically significant difference among groups.
Keywords: Education -- Computer network resources.; Teaching -- Computer network resources.; Internet in education.; Computer-assisted instruction.